Does tourism development, energy consumption, trade openness and economic growth matters for ecological footprint: Testing the Environmental Kuznets Curve and pollution haven hypothesis for Pakistan. (15th April 2022) - Liu, Yaping; Sadiq, Farah; Ali, Wajahat; Kumail, Tafazal
Abstract: The present study investigates the Environmental Kuznets Curve relationship between travel and tourism and ecological footprint in Pakistan over the period 1980–2017. For this purpose, the impact of tourism development, economic growth, energy consumption, trade openness and foreign direct investments on ecological footprint is empirically examined within the EKC framework. The ARDL bounds and Bayer and Hanck tests indicate that variables in this study have long-term cointegration. Results revealed a tourism-led growth hypothesis and an inverted U-shaped relationship between travel and tourism and ecological footprint in Pakistan. The ARDL and Toda-Yamamoto non-causality results also reveal that energy use and trade openness are at the cost of ecological footprint. Moreover, inflow of foreign direct investment also adds environmental degradation and support pollution haven hypothesis. Thus, sustainable tourism, fuel mix variation and services sector oriented foreign direct investment should be the target of policymakers. Highlights: This paper inspect the tourism-led-growth and EKC hypothesis. Both conventional and new turning point formulas reveals EKC hypothesis between travel & tourism and EF. Results show that FDI deteriorates environmental quality and support pollution haven hypothesis. International Trade in Pakistan is environment friendly.